BIOAVAILABILITY STUDY OF SAMBILOTO (Andrographis paniculata) HERBS INFUSION IN RABBIT - Jutti Levita (Indonesian Journal of Pharmacy, 2014)
Andrographis paniculata or sambiloto is one of the most widely used medicinal herbs in Indonesia. The main bioactive chemical constituent, andrographolide, has been reported to have various pharmacological activities. Besides its function for medical purposes, the sambiloto herbs infusion is frequently taken to maintain health. This study was conducted to determine the bioavailability of sambiloto herbs infusion in rabbit plasma, stomach, and liver, calculated as total andrographolide. Fourteen male New Zealand white rabbits were used in this study. Sambiloto herbs infusion were administered orally at the dose 7.04mL/kg body weight to each rabbit. Blood samples were taken at intervals 0.0; 0.5; 1.5; 2.0; 3.0; and 5.0h after infusion administration. Sambiloto herbs infusion, which are calculated as andrographolide, levels in plasma, stomach, and liver were analyzed by high performance liquid chromatography using C-18 column as stationary phase and a mixture of methanol-double distilled water (60:40) as mobile phase. Bioavailability parameters obtained were Cmax 0.5549µg/mL (in stomach), 0.2136µg/mL (in plasma), 0.0051µg/mL (in liver); while tmax 1h (in stomach), 1.5h (in plasma), 2h (in liver); and AUC 1.7451µg.h/mL (in stomach), 0.434µg.h/mL (in plasma), 0.0038µg.h/mL (in liver). These data showed that in healthy animals, sambiloto herbs infusion was fastly absorbed from the stomach, distributed in the circulation system, and metabolized in the liver, in subsequent process. Sambiloto herbs infusion showed good bioavailability in rabbit.